A finite difference scheme for a fluid dynamic traffic flow model appended with two-point boundary condition - Gani, MO; Hossain, MM; Andallah, LS (GANIT: Journal of Bangladesh Mathematical Society, 2012)
A fluid dynamic traffic flow model with a linear velocity-density closure relation is considered. The model reads as a quasi-linear first order hyperbolic partial differential equation (PDE) and in order to incorporate initial and boundary data the PDE is treated as an initial boundary value problem (IBVP). The derivation of a first order explicit finite difference scheme of the IBVP for two-point boundary condition is presented which is analogous to the well known Lax-Friedrichs scheme. The Lax-Friedrichs scheme for our model is not straight-forward to implement and one needs to employ a simultaneous physical constraint and stability condition. Therefore, a mathematical analysis is presented in order to establish the physical constraint and stability condition of the scheme. The finite difference scheme is implemented and the graphical presentation of numerical features of error estimation and rate of convergence is produced. Numerical simulation results verify some well understood qualitative behavior of traffic flow. DOI: http://dx.doi.org/10.3329/ganit.v31i0.10307 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 31 (2011) 43-52